Changes in the Structure of Earnings During the Polish Transition - Prasad, Eswar (IMF Working Papers; Working Paper ;, 2002)
This paper documents that inequality in labor earnings increased substantially during the economic transition in Poland. One surprising result is that earnings inequality increased markedly in both the private and public sectors, indicating that even state-owned enterprises in Poland moved toward competitive wage setting during the transition. Education premia increased sharply, while experience premia declined. Increases in within-group inequality account for about 60 percent of the increase in overall wage inequality. But, contrary to the experience of countries like the United States, increases in within-group inequality in Poland were very different across skill groups, with much larger increases for highly educated workers.